Mental health care: how can Family Health teams integrate it into Primary Healthcare? - Gryschek, Guilherme; Marques Pinto, Adriana Avanzi [UNESP] (Abrasco, 2015)
Mental health is one of the responsibilities of Brazil's Family Health system. This review of literature sought to understand what position Mental Health occupies in the practice of the Family Health Strategy. A search was made of the scientific literature in the database of the Virtual Health Library (Biblioteca Virtual de Saude), for the keywords: 'Mental Health'; 'Family Health'; 'Primary Healthcare'. The criteria for inclusion were: Brazilian studies from 2009 through 2012 that contributed to understanding of the following question: How to insert Mental health care into the routine of the Family Health Strategy? A total of 11 articles were found, which identified difficulties and strategies of the professionals in Primary Healthcare in relation to mental health. Referral, and medicalization, were common practices. Matrix Support is the strategy of training and skill acquisition for teams that enables new approaches in mental health in the context of Primary healthcare. It is necessary for Management of the Health System to take an active role in the construction of healthcare networks in mental health.
Keywords: Primary healthcare; Mental health; Family Health